Business Intelligent as Survivalability Strategy of Women Entrepreneurs in Malaysia - Fuad, Nurwahida; Bohari, Abdul Manaf (Journal of Asian Business Strategy, 2012)
In general, Business Intelligence (BI) is the sophistication of the gathering, integrating and utilizing data from various sources, and synthesizing results in a version that can enhance business sustainability. BI provides sufficient fundamentals for gear-up related process of business survivalability. Thus, nowadays, women entrepreneurs firm desire to use and apply their strategy into BI systems, which involve a precise evaluation to the business advantages. This paper describes the fact that competitive advantage can be gained through BI as survivability strategy for women entrepreneurs in the small and medium sized industry in Malaysia. Secondly, this paper aimed to evaluates the impact of BI on improving business strategy to evaluating the accurate of the women entrepreneurs firm in competitive market environment. Thus, the need to strengthening Malay women entrepreneur competitive level is a vital important to fostering the greater capacity of them, especially for achieved global standard of technological and innovation. Finally, some aspect of business strategy is discussed for establish good integration with business intelligent.